Comparative plastomes sheds light on phylogeny of Weigela - Wang, Lei; Li, Fuxing; Zhao, Kexin; Yang, Jie; Sun, Haonan; Cui, Xingyong; Dong, Wenpan; Li, Enze; Wang, Ning (Frontiers in Plant Science, 2024)
Weigela Thunb. is a genus in the family Caprifoliaceae. All species in this genus have high ornamental and medicinal value. However, the genetic divergence between species and the phylogeny within Weigela is still unclear. Therefore, we sequenced and analyzed four plastomes from four different Weigela species to reveal the genetic divergence among species of this genus, and the phylogeny within Weigela.The four plastomes from Weigela ranged from 156,909 bp to 157,739 bp in size, and presented a typical circular quadripartite structure. Each complete plastome contained a pair of inverted repeat regions (23,592~24,957 bp), a larger single-copy (LSC) region (89,922~90,229 bp), and a small single-copy (SSC) region (17,668~20,429 bp). We identified three types of repeats, corresponding to 268 forward repeats, 128 palindromic repeats, and 867 tandem repeats, for a total of 1,263 long repeats. A total of 352 SSRs were identified from the four plastomes, and most of them were concentrated in the LSC region and the noncoding regions. Mononucleotide repeat units were the most frequently detected types of repeats, of which A/T repeat units were the most abundant.Three mutational hotspots (trnH-psbA, trnR-ndhF, and trnN-ndhF) were identified as candidate barcodes for Weigela species. Weigela belongs to Diervilloideae located at an early diverging position in the Caprifoliaceae. Within Weigela, W. japonica and W. floribunda were sister with W. subsessilis and W. florida. This study revealed the plastome structure and variation of four well-known Weigela species, and found three candidate barcodes for further study of four well-known Weigela species. In addition, the phylogenetic location of Weigela within the Caprifoliaceae was identified.